Atypical Presentation of Rocky Mountain Spotted Fever in Pregnancy - Jenny Wu; Sarah K. Dotters-Katz; Megan Varvoutis (Thieme Medical Publishers, Inc., 2024)
Rocky Mountain spotted fever (RMSF) is a common tick-borne disease and can have variable presentation with potentially fatal outcomes when untreated. We describe an atypical presentation of RMSF in the third trimester. A 37-year-old multiparous woman at 310/7 weeks' gestation presented normotensive with headaches and fever but no rash or significant tick exposure. She was initially treated for atypical hemolysis, elevated liver enzymes, and low platelet count syndrome but further decompensated, requiring intensive care unit transfer, intubation, and emergent delivery. Doxycycline administration was associated with marked improvement with no significant sequalae to mother or infant. Later convalescent serologies were positive for RMSF. RMSF is a clinically challenging diagnosis in pregnancy. Given significant morbidity and mortality associated with delayed treatment, high suspicion in endemic areas is needed, and prompt antibiotic use with doxycycline should be administered.